2017
DOI: 10.1371/journal.pone.0189089
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing household survey methods to monitor the Sustainable Development Goals targets 6.1 and 6.2 on drinking water, sanitation and hygiene: A mixed-methods field-test in Belize

Abstract: BackgroundThe Sustainable Development Goals (SDGs) require household survey programmes such as the UNICEF-supported Multiple Indicator Cluster Surveys (MICS) to enhance data collection to cover new indicators. This study aims to evaluated methods for assessing water quality, water availability, emptying of sanitation facilities, menstrual hygiene management and the acceptability of water quality testing in households which are key to monitoring SDG targets 6.1 and 6.2 on drinking Water, Sanitation and Hygiene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 16 publications
1
40
0
6
Order By: Relevance
“…A multitude of studies focused on women and girls and demonstrated that women practiced poor sanitation, hygiene, and MHM practices, largely due to lacking resources. Sanitation facilities were commonly cited to not be safe, clean, and accessible (Kwiringira et al, 2014;Sato et al, 2016;Khan et al, 2017;Aluko et al, 2018;Angoua et al, 2018;Dendup et al, 2018;Desalegn et al, 2018;Njuguna, 2019;Winter et al, 2019). Basic needs, such as soap and washing facilities, and hygienic products, such as toothpaste were documented as hygiene barriers (Budhathoki et al, 2018;Lubon et al, 2018).…”
Section: Women Face Unique Wash and Mhm Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…A multitude of studies focused on women and girls and demonstrated that women practiced poor sanitation, hygiene, and MHM practices, largely due to lacking resources. Sanitation facilities were commonly cited to not be safe, clean, and accessible (Kwiringira et al, 2014;Sato et al, 2016;Khan et al, 2017;Aluko et al, 2018;Angoua et al, 2018;Dendup et al, 2018;Desalegn et al, 2018;Njuguna, 2019;Winter et al, 2019). Basic needs, such as soap and washing facilities, and hygienic products, such as toothpaste were documented as hygiene barriers (Budhathoki et al, 2018;Lubon et al, 2018).…”
Section: Women Face Unique Wash and Mhm Challengesmentioning
confidence: 99%
“…A small fraction (6%) of studies focused on the role of MHM, where women reported a lack of proper MHM products, such as clean pads, in addition to private areas and an absence of water provisioning for cleaning and sanitation needs (Khan et al, 2017;Budhathoki et al, 2018;Davis et al, 2018). Davis et al (2018) demonstrated how one in 10 students missed school due to menstruation, and this could, in part be attributed to menstrual stigma.…”
Section: (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the data requirements for SDG monitoring, new questions and modules have been developed for inclusion in household surveys [14]; however, information on the quality of drinking water and sanitation services can more appropriately be obtained from government authorities that have regulatory oversight of service providers, and a mandate to monitor and value water resources and services [15]. …”
Section: Introductionmentioning
confidence: 99%
“…9 Increased recognition of the importance of menstrual hygiene, and attention to the special needs of women and girls stated in Sustainable Development Goal (SDG) 6.2, mean PMA2020 may soon be joined by other largescale surveys seeking to monitor women's menstrual needs and practices. 10 In breaking new ground to provide the first national estimates of women's menstrual hygiene practices, PMA2020 data can offer unique insights into current needs and identify emerging measurement challenges. Using mobile-based data collection, the PMA2020 survey methodology applies automatic question filtering based on past answers to streamline the survey process and ensure respondents are only asked questions that are relevant to them.…”
Section: Introductionmentioning
confidence: 99%